2016
DOI: 10.1007/s11250-016-1201-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of leptospirosis on dogs, pigs, and horses in Latin America

Abstract: Leptospirosis is a worldwide zoonosis which can affect many species. Control programs need accurate diagnosis to be successful, and currently, diagnosis relies on serology. It presents three main issues: the sampling, the antigen panel, and the cutoff point. Herein, we propose a systematic review on leptospirosis among dogs, pigs, and horses in Latin America in order to improve the understanding of the seroepidemiology of leptospirosis in these species in the region as well as the temporal development of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 36 publications
5
47
1
4
Order By: Relevance
“…The low antibody titre suggested that the circulating strain in the swine unit belonged to one of those described of maintenance serovar in pigs. The serogroups mostly found in swine are Pomona, Australis, Tarassovi and Sejroe [ 14 , 20 , 21 , 22 , 23 ], albeit also other serogroups such as Autumnalis, Ballum, Bataviae, Pyrogenes, Grippotyphosa, Icterohaemorrhagiae and Canicola are observed in surveillance studies [ 21 , 24 , 25 , 26 , 27 ]. The predominant serogroup found in the swine unit was Autumnalis, followed by Australis, Tarassovi and Ballum.…”
Section: Discussionmentioning
confidence: 99%
“…The low antibody titre suggested that the circulating strain in the swine unit belonged to one of those described of maintenance serovar in pigs. The serogroups mostly found in swine are Pomona, Australis, Tarassovi and Sejroe [ 14 , 20 , 21 , 22 , 23 ], albeit also other serogroups such as Autumnalis, Ballum, Bataviae, Pyrogenes, Grippotyphosa, Icterohaemorrhagiae and Canicola are observed in surveillance studies [ 21 , 24 , 25 , 26 , 27 ]. The predominant serogroup found in the swine unit was Autumnalis, followed by Australis, Tarassovi and Ballum.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic Leptospiras are the etiological agents of leptospirosis, an emerging zoonotic disease that affects humans and animals worldwide [ 2 ]. Leptospirosis may affect many species including domestic and wild animals [ 3 , 4 ]. In humans, most characteristic early clinical signs include fever of sudden onset, severe general malaise, muscular pain, and conjunctival congestion [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria of the genus Leptospira cause leptospirosis, which is a zoonotic disease of global importance [ 9 , 10 ]. Infection with Leptospira occurs in more than 160 species of domestic and wild animals [ 11 ].…”
Section: Introductionmentioning
confidence: 99%